2020
DOI: 10.1002/pen.25498
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide reinforced PET/PBT nanocomposites: Compatibilization and characterization

Abstract: This research work focused on the effects of different compatibilizers on the properties of reduced graphene oxide (rGO) reinforced poly(ethylene terephthalate) (PET)/poly(butylene terephthalate) (PBT) nanocomposites. The samples were prepared via melt compounding and injection molding methods. The Joncryl and glycidyl isooctyl polyhedral oligomeric silsesquioxane (GPOSS) were used as compatibilizers at different loading levels (0.5%-4%). The structural, thermal, mechanical, morphological, and electrical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…[ 28,29 ] In various studies investigating the effects of graphene and other nanofillers on T g , it has been reported that T g can be affected positively [ 8,26 ] or negatively. [ 6,30,31 ] The decrease in T g can be attributed to the weak interfacial interaction between the GO and PET/PBT matrix which increases the mobility of segmental chains. According to Pandis et al [ 32 ] the interfacial interactions are weak in nano‐silver reinforced PMMA nanocomposites and therefore the molecular packing of polymeric chains near the nanoparticles is loose.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 28,29 ] In various studies investigating the effects of graphene and other nanofillers on T g , it has been reported that T g can be affected positively [ 8,26 ] or negatively. [ 6,30,31 ] The decrease in T g can be attributed to the weak interfacial interaction between the GO and PET/PBT matrix which increases the mobility of segmental chains. According to Pandis et al [ 32 ] the interfacial interactions are weak in nano‐silver reinforced PMMA nanocomposites and therefore the molecular packing of polymeric chains near the nanoparticles is loose.…”
Section: Resultsmentioning
confidence: 99%
“…There are various studies in which silica is added to PET/PBT blend and various fillers such as organoclay, GO, graphene nanoplatelet (GNP) are added to PET. [ 3,5,6,8,9 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, graphene oxide (GO) and reduced graphene oxide (rGO) have attracted much attention due to their ability to enhance mechanical, thermal, electrical, and especially gas barrier properties of rubber composites. [ 1,28–40 ] However, the effects of GO and its derivatives on the kinetics of sulfur vulcanization in such systems has not been studied. There is no appropriate affinity between nonpolar elastomers and highly polar GO.…”
Section: Introductionmentioning
confidence: 99%